Stigmatization of Delinquent Children and Those in Conflict with the Law - Meliana Kartika Herningsih; R. Rahaditya (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
This research examines Indonesia's legal framework through Law Number 11 of 2012 on the Juvenile Criminal Justice System (SPPA), which implements principles of restorative justice and diversion to protect children from stigmatization. Using normative juridical research with a legislative approach, this study analyzes how criminal policies based on restorative justice can prevent stigma while providing opportunities for behavioral improvement outside the formal legal process. The SPPA Law comprehensively regulates the protection of children's rights, particularly rehabilitation over punishment. Diversion offers a humane alternative that prevents developmental trauma and stigma. However, its implementation faces challenges including inadequate understanding of restorative justice principles among law enforcement officials and continuing negative public perceptions of children undergoing diversion. This research proposes strategies to strengthen restorative approaches that better protect children's futures while maintaining accountability.